2023
DOI: 10.1097/ms9.0000000000000684
|View full text |Cite
|
Sign up to set email alerts
|

Mutation in PYCR2 gene and hypomyelinating leukodystrophy in children: a case report study

Abstract: Introduction and importance: Hypomyelinating leukodystrophies are a heterogeneous group of inherited white matter disorders characterized by a predominant absence of myelin deposits in the central nervous system. Case presentation: The patient was a one-year-old girl child. She at the age of 6 months was hospitalized due to loose, muscle weakness, and an upward gaze for 7–8 min with complaints of fever and convulsions. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 15 publications
0
1
0
Order By: Relevance
“…After the first report of Nakayama et al,around 40 patients have been reported so far (Aaltio et al, 2024;Afroze & Mercimek-Andrews, 2020;Hosseini & Ghelichi-Ghojogh, 2023;Manaspon et al, 2021;Meng et al, 2017;Nakayama et al, 2015;Zaki et al, 2016). There was an adult patient from a Chinese case report, while all others were under the age of 20 (Xie et al, 2021).…”
Section: Introductionmentioning
confidence: 97%
“…After the first report of Nakayama et al,around 40 patients have been reported so far (Aaltio et al, 2024;Afroze & Mercimek-Andrews, 2020;Hosseini & Ghelichi-Ghojogh, 2023;Manaspon et al, 2021;Meng et al, 2017;Nakayama et al, 2015;Zaki et al, 2016). There was an adult patient from a Chinese case report, while all others were under the age of 20 (Xie et al, 2021).…”
Section: Introductionmentioning
confidence: 97%